The Effect of Nutritional and Environment Information on Consumer’s Willingness-to-pay (WTP) for Products Containing an Upcycled Ingredient - Le, Nguyen Doan Duy; Huynh, Diep My Phung; Nguyen, Quoc Cuong (JST: Engineering And Technology For Sustainable Development, 2025)
This research aims to introduce upcycled food to Vietnamese consumers and investigate which information affects willingness to pay for an upcycled food, that is biscuit products adding spent coffee grounds (SCG). A choice experiment was conducted with more than 200 consumers. Using Multinominal Logit Model (MNL) and Mixed Multinominal Logit Model (MMNL), it is found that the consumers concerned about three information price, antioxidant, coffee flavour, and not pay attention to type of flour, carbon trust information. Among the relevant information, consumers are willing-to-pay a premium of 31.4 thousand VND and 19.6 thousand VND for antioxidant ingredient and coffee flavour.